Culture in translation: A comparative analysis of English originals and Polish dubbed versions of computer-animated film productions - Surdyk, Augustyn (Vandenhoeck & Ruprecht Verlage, 2020)
The aim of the research presented in this chapter was to indicate the multiplicity of culture-related references in audio-visual English-Polish translation on the example of a longer form, which is a computer animated film containing humorous elements. The film selected for the analysis is the Polish dubbed version of the American blockbuster from 2004 Shrek 2. The culture-related fragments detected and analysed have been divided into four categories and marked out as: 1) linguistic references (quotations or paraphrases from popular Polish books, films and songs); 2) cultural references (expressions or proper names known and characteristic exclusively of Polish culture); 3) everyday language (popular, colloquial and slang sayings, idiomatic expressions, proverbs, language styled to be archaic and elements of regional dialects); 4) personal references to well known Poles, celebrities and fictional characters. As a result of the analysis undertaken, 90 culture-related film script fragments were detected. Moreover, having been confronted with the original version, in many cases they seem to be much funnier than the original phrases.
Keywords: audio-visual translation; dubbing; computer animated films; humour; culture